A designação beneficiária e os herdeiros legais no contrato de seguro de vida - Babo, Adriana Sofia Araújo de (2018)
In this paper we intend to analyze the issue of generic beneficiary designation in favor of heirs in life insurance, taking into account the position of the life insurance contract in the legal regulatory framework, in line with the interpretation of the respective beneficiary clause, delimiting the extension of the concept of legal heir to that effect and to what title the benefit must be acquired by him, as well as the impact of the application of the rules on inheritance law in the definition of the concept of heir. We will also consider cases in which the heirs acquire the right to benefit as a result of the lack of beneficiary designation or rejection of the benefit from the designated third party, once the insurance capital will return to the assets of the person that paid the premiums. On the same line, in insurance on the life of one self, the insurance capital must integrate the patrimony of the mentioned party, which will become part of his inheritance, being transmitted to his heirs by succession. As a result of the beneficiary designation "in favor of the heirs", a number of issues arise, frequently raised in insurance practice, particularly regarding the reach of the concept of heir to that effect. In analyzing Article 201º nº3 a), the term "legitimate succession" arises, but we believe that this precept should be interpreted in a broad sense, extending it to cases in which the de cujus distributes its mass of the inheritance by means of a will, as to the legatee heirs, in cases in which the de cujus has distributed all of his inheritance in legacies. On the other hand, the application of the rules on inheritance law to determine the concept of heir will result in cases of unworthiness and disinheritance, as an obstacle to the acquisition of heir and, consequently, beneficiary status, in cases where the benefit reverts in favor of the heirs. Although the heirs acquire the right to the benefit "iure stipulationis" and not by succession. In short, we believe that the beneficiary clause "in favor of heirs" has implications on inheritance, so we must rely on the rules laid down in this scope, both to determine the concept of heirs and to determine the value of the benefit to be made by the insurer.